Preparation of meso-Ag/Al2O3 and synergistic water disinfection of metallic silver and ROS under visible light. (October 2018) - Chen, Huajun; Tian, Wenjie; Ding, Wuxiu
Highlights: Metallic sliver-doped mesoporous Al2 O3 fibers (meso-Ag/Al2 O3 ) was successfully achieved. The meso-Ag/Al2 O3 can harvest visible light and speed up solar water purification. The disinfection mechanism of meso-Ag/Al2 O3 was the cooperating results of the metallic silver and the reactive oxygen. Water disinfection of >99.999% inactivation of bacteria in 120 min with a small amount of material (8 mg/L) was achieved. Abstract: Metallic sliver-doped mesoporous Al2 O3 fibers (meso-Ag/Al2 O3 ) that can harvest visible light to speed up solar water purification, were synthesized by one-pot hydrothermal method. Insightful analyses of XRD, XRF and XPS of meso-Ag/ Al2 O3 verified that metallic silver occupied interstitial positions of Al2 O3 lattice forming interstitial solid solution. N2 adsorption/desorption illustrated that meso-Ag/Al2 O3 exhibited significantly increases in the specific surface area, pore volume and average pore diameter after doping with silver. The UV–Vis diffuse reflectance spectra and disinfection performance indicated that meso-Ag/Al2 O3 can harvest visible light to promote the conversion of dioxygen to ROS for water disinfection compared with the widely used TiO2 . With our approach, we achieved water disinfection of >99.999% inactivation of bacteria in 120 min with a small amount of material (8 mg/L) under simulated visible light.